â€œNgaji dan Sholawatâ€: Bentuk Eksistensi dan Dinamika Sosial Dakwah Safari Majelis Sholawat di Jayapura-Papua - Amri, Amri; Munir, Misbahul; Purwati, Heni (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2024)
This paper aims to find out how the form of existence and Social Dynamics of Da'wah through "Ngaji Dan Sholawat" conducted by the Safari Team of the Sholawat Council of Jayapura City. The method used in this study is descriptive qualitative, which is a method that is explained through detailed facts in the field by observing and participating in da'wah activities, interviews, to documentation Photos and videos of "Ngaji and Sholawat" activities. The results showed that the existence of their da'wah as a form of caring for Islamic culture through sholawat by considering the success of the implementation of da'wah, the target of da'wah, the da'wah environment to the media as their da'wah infrastructure. Furthermore, the social dynamics experienced towards da'wah "Ngaji Dan Sholawat is the acceptance of da'wah safari team majelis sholawat (SMS) for Muslims in Jayapura City. The form of acceptance of da'wah through "Ngaji and Sholawat is the enthusiasm of the community in participating in their activities and da'wah as a place to change attitudes of faith behavior in Allah swt.